Density and viscosity for the ternary mixture of 1, 3, 5-trimethyladamantane + 1, 2, 3, 4-tetrahydronaphthalene + n-octanol and corresponding binary systems at T = (293.15 to 343.15) K. (May 2022) - Qin, Xiaomei; Yang, Shihao; Zhao, Jianbo; Wang, Lan; Zhang, Yingying; Qin, Xiaoyun; Luo, Dan
Highlights: Density and viscosity for the mixtures (1, 3, 5-trimethyladamantane + 1, 2, 3, 4-Tetrahydronaphthalene + n -octanol) were investigated. Excess properties and viscosity deviations for the mixtures were calculated and analyzed. The nonideal behaviors of the V m E and Δ η can be attributed to the change of the structural effect and hydrogen bond force between molecules. Abstract: Densities and viscosities for the ternary mixture, 1, 3, 5-trimethyladamantane (1, 3, 5-TMA) + 1, 2, 3, 4-Tetrahydronaphthalene + n -octanol, and their corresponding binary mixtures (1, 3, 5-TMA + 1, 2, 3, 4-tetrahydronaphthalene, 1, 3, 5-TMA + 1-octanol, and 1, 2, 3, 4-tetrahydronaphthalene + 1-octanol) have been determined over the whole composition range at different temperatures ranging from 293.15 K to 343.15 K. The excess molar volume (V m E ) and the viscosity deviation (Δ η ) for these binary and ternary systems were calculated and then fitted to the Redlich–Kister equation. The V m E values are negative for the nonpolar system of 1, 3, 5-TMA and 1, 2, 3, 4-tetrahydronaphthalene. For the systems containing 1-octanol, the V m E values become positive with increasing temperature. The V m E values for the ternary system are partially negative, and they increase against the temperature. All the Δ η values show negative deviations for the measured binary and ternary mixtures and increase obviously with enhancement in temperature. In addition, the nonideal behaviors of excess properties and viscosity deviations for the mixtures were analyzed. The measured and correlation results could supplement basic data for the design and modelling of high-energy-density hydrocarbon fuels.